Benchmark on Main Applications for Hardox Bars and Tubes - Spolander, Felix; Södervall, Stefan (My University, 2021)
Hardox bars and tubes are a relatively new product for SSAB, which were introduced 3 respectively 7 years ago in the market. The products are characterised by its excellent strength and toughness properties. SSAB is confident that Hardox bars and tubes are competitive products. However, this is not reflected by current sales, there is an unrealised potential as segments, applications and customer value is not yet fully explored. While Hardox tubes and bars are similar in terms of product characteristics and shape, the products are significantly different with regards to applications and how they provide value to the customer. Because of these differences, the products were investigated and analysed separately. For Hardox tubes, six segments were defined that categorize the main industries and present the main applications. The applications where larger market potential and attractiveness exists are: mining transportation pipes for hydraulic ore hoisting and paste backfilling, drilling pipes for reverse circulation, down the hole and diamond core drill rigs, industrial process transportation pipes for FCC catalyst and zeolite production, and concrete pumping trucks. For Hardox bars several potential applications across the targeted segments have been identified. It can be concluded that the potential for high volume applications is limited due to barriers related to the price of the product offering and incompatibilities with the customers capabilities. As a result, the discussion regarding Hardox bars focuses on how to overcome these challenges by routing the product offering through distributors.
Keywords: Product Management, Marketing, Business Development, Market Analysis, Competitor Analysis, Value Analysis, Business-to-Business